Activated carbon supported CaO for conversion of palm oil to biodiesel Kinetic experiment - Kidan, Tsegay G.; Habtu, Nigus G. (Ethiopian Journal of Science and Technology, 2025)
Biodiesel is one of the bio-energies prepared from vegetable o i l or animal fat through transesterification reaction wi t h methanol. Because of the separation cost a n d associated environmental problems of homogeneous catalyzed biodiesel production, utilization of basic heterogeneous catalysts is steadily increasing in recent years. CaO is among the most solid base catalysts which can be used in transesterification reaction. In this study, activated carbon supported CaO catalyst was used for the transesterification reaction of palm oil. The catalyst was prepared according to the conventional incipient witness impregnation method. Kinetic experiment was performed in a batch reactor in the presence of heterogeneous catalyst for a wide range of operating conditions. The progress of the reaction was monitored using the refractive index method. Response surface methodology coupled with the central composite design was used to screen out t h e operating conditions and optimize the experimental result. A conversion of 34.78% was found at set of optimized conditions (reaction time of 150 min, temperature o f 59.5 0C, methanol to oil molar ratio of 19.40:1, and amount of catalyst loaded o f 10.55 (wt.%)). The predicted values of the response surface model were found in a good agreement with the actual experimental values at the aforementioned operating conditions. Moreover, the experimental result demonstrated that a pseudo-first order kinetic model best explains the transesterification reaction. Using graphical method from t h e Arrhenius equation, the value of activation energy and pre-exponential factor were calculated to be 35.16 kJ mol-1 and 731.43 kJ mol-1, respectively.